Some Selected Phytoconstituents from Rhus succedanea as SARS CoV-2 Main Protease and Spike protein (COVID-19) Inhibitors: Selective Phytoconstituents from Rhus succedanea against SARS CoV-2: In silico approach - D. S. N. B. K., Prasanth; Achanta, Suneetha; Prasad Panda, Siva; Rao Atmakuri, Lakshmana; Guntupalli, Chakravarti; Rao Alla, Narayana; Jamullamudi, Risy Namratha; Mohammed, Jahasultana; Lanka, Haritha; Nayudu, Teja; Tera, Sandhya; Koti, Bhargavi; et al. (Iranian Journal of Pharmaceutical Sciences, 2021)
Rhus succedanea (Anacardiaceae) was used to treat multiple human afflictions. Literary works demonstrate that it has many biological activities. Today's research aims to recognize Rhus succedanea Phyto-derived anti-viral compounds against the main protease and spike protein of the viral agent of COVID-19 (SARS-CoV-2) gain insight into the molecular interactions. In the current study, ten molecules taken from R. succedanea are analyzed through docking, derived from the PubChem database. Docking experiments with Autodock vina and PyRx tools were conducted. AdmetSAR and DruLito servers were eventually used for drug-like prediction. Our research shows that the phytoconstituents from R. succedanea, namely, Amentoflavone, Rhoifolin, and Agathisflavone acts against SARS CoV-2 main protease with the binding affinity of -9.3, -8.6 and -8.4 Kcal/mol; Hinokiflavone Robustaflavone and Amentoflavone acts against the SARS-CoV-2 receptor-binding domain of spike protein with a binding affinity of -10.5, -10.4 and -10.1 Kcal/mol respectively. These phyto-compounds can use contemporary strategies to develop effective medicines from natural origins. The substances identified potential anti-viral as likely. However, In-vitro studies are even more necessary to assess their effectiveness versus SARS CoV-2.